Adaptation and validation of the Malay version of Daily Record of Severity of Problems (DRSP) among undergraduate students in a University in Malaysia - Hasim @ Hashim, Siti Inarah; Abdul Khaiyom, Jamilah Hanum (Malaysian Psychiatric Association, 2019)
Premenstrual Dysphoric Disorder (PMDD) is a newly categorized mental disorder in DSM-5. It impacted about 1.8% to 5.8% of women population in the United States. However, no information was found on the prevalence rate of PMDD in Malaysia context. This may be due to lack of reliable and valid instruments to assess the disorder for the local populations. Hence, current study aims to address this issue by validating the Malay adapted version of Daily Record of Severity of Problems (DRSP), one of the scale designed to assess the disorder. The current study protocol will inform the procedures of the exploratory-based validation study. Using survey research design, 350 samples of undergraduate students from a university in Klang Valley, Malaysia will be recruited for this research. The psychometric properties of DRSP in terms of reliability (internal consistency and test-retest reliability) and validity (concurrent, convergent, divergent, and factor structure) will be analysed. It is hoped the results of the study will facilitate further research on PMDD in Malaysia.